Novel medical and general. - Bos, Gerrit, 1948- (Middle East and Islamic Studies E-Books Online, Collection 2019, ISBN: 9789004386341., 2018)
This volume is part of a wider project aiming at mapping the technical medical terminology as it features in medieval Hebrew medical works, especially those terms that do not feature in the current dictionaries at all, or insufficiently. In this way the author hopes to facilitate the consultation of these and other medical works and the identification of anonymous medical material. The terminology discussed in this volume has been derived from three primary and seven secondary sources. The primary sources are: (1) Sefer Ṣedat ha-Derakhim - Moses Ibn Tibbon's translation of Ibn al-Jazzār's Zād al-musāfir , bks. 1-2; (2) Sefer ha-Shimmush - Shem Tov Ben Isaac's Hebrew translation of al-Zahrāwī's Kitāb al-taṣrīf ; (3) Sefer ha-Qanun - Nathan ha-Meʾati's Hebrew translation of the first book of Ibn Sīnā's K. al-Qānūn .